Exploring the Split-Hand Phenomenon in ALS with Motor unit Number Index (MUNIX) - Abramova, A. A.; Broutian, A. G.; Zakharova, M. N. (Human physiology, 2021)
Split-hand phenomenon in amyotrophic lateral sclerosis (ALS) is characterized by uneven progression of muscle weakness in the intrinsic hand muscles, with predominant wasting of abductor pollicis brevis (APB) and first dorsal interosseus muscles over abductor digiti minimi (ADM) muscle. The aim of the study was to evaluate the split-hand phenomenon in ALS patients using motor unit index (MUNIX). Fifty-six patients diagnosed with definite and probable ALS according to El Escorial criteria were enrolled in the study. Twenty-seven patients (48.2%) had bulbar-onset ALS, while twenty-nine patients (51.8%) presented with spinal-onset ALS. Clinical measures including disease duration, disease stage according to the King’s College staging system, and ALSFRS-R score were evaluated for each patient. The control group consisted of twenty-two healthy subjects with normal findings on nerve conduction studies of the upper extremities. Both APB and ADM were studied, and ratios (APB/ADM) of the compound muscle action potential (CMAP) and MUNIX were assessed. Although CMAP and MUNIX ratios were lower in ALS than in healthy controls, this reached statistical significance only for the MUNIX ratio. No correlations were found between electrophysiological data (MUNIX and CMAP ratios) and clinical measures in the ALS group, which could be caused by high clinical heterogeneity in the ALS group. Our findings correspond to the literature data on high diagnostic sensitivity of MUNIX in assessing the split-hand phenomenon. MUNIX is a promising tool for evaluation of the split-hand phenomenon, which can be widely used both for analyzing mechanisms of disease pathology in longitudinal studies and improving early diagnosis of the disease.